2006
DOI: 10.1182/blood-2006-07-036012
|View full text |Cite
|
Sign up to set email alerts
|

Trough imatinib plasma levels are associated with both cytogenetic and molecular responses to standard-dose imatinib in chronic myeloid leukemia

Abstract: Using high-performance liquid chromatography-tandem mass spectrometry, we assessed trough imatinib plasma levels in 68 patients with chronic myeloid leukemia (CML) who responded or not to standard-dose imatinib, after at least 12 months' treatment. Mean trough imatinib plasma levels were significantly higher in the group with complete cytogenetic response (56 patients) than in the group without (12 patients; P ‫؍‬ .03) and higher in the group with major molecular response (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

38
499
7
10

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 547 publications
(554 citation statements)
references
References 18 publications
38
499
7
10
Order By: Relevance
“…Moreover, in patients with an MMR, the median trough concentration (1020 ng ml -1 ) was greater than the 1002 ng ml -1 threshold reportedly required for efficacy, 5 further supporting the observed statistical association between plasma IM levels and clinical response. In addition, our study identified a significant correlation between ABCG2 421C4A (p.Q141K) and IM trough concentration, suggesting an important role for the BCRP efflux transporter in IM metabolism.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Moreover, in patients with an MMR, the median trough concentration (1020 ng ml -1 ) was greater than the 1002 ng ml -1 threshold reportedly required for efficacy, 5 further supporting the observed statistical association between plasma IM levels and clinical response. In addition, our study identified a significant correlation between ABCG2 421C4A (p.Q141K) and IM trough concentration, suggesting an important role for the BCRP efflux transporter in IM metabolism.…”
Section: Discussionsupporting
confidence: 69%
“…3 Recently, two studies suggested that plasma IM trough concentration variability influences clinical response among CML patients. 4,5 In addition, Picard et al reported that the threshold for IM trough concentration should be set above 1002 ng ml -1 , as this level was significantly associated with a major molecular response (MMR). 5 Although several important clinical trials indicated that 400 mg of IM should be the standard daily dose for chronic phase CML patients, 1,2 in clinical practice, lower doses of IM are administered to B40% of Japanese patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…c o m / l o c a t e / c l i n b i o c h e m to treatment, which, in turn, correlates with clinical outcome [3]. Picard et al determined that the ideal trough IM plasma concentration should be at least 1000 ng/mL [4].…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…Preliminary experiments showed that these concentrations are sufficient to completely inhibit irradiation-induced c-Abl activity in all cell lines used (not shown). The concentrations are in the range of those found in plasma from patients treated with 400 or 600 mg imatinib (Picard et al, 2007). The HPRT mutation frequency was evaluated as described (van der Kuip et al, 2004).…”
Section: Introductionmentioning
confidence: 99%